Case‐control study of hepatitis B and hepatitis C in older adults: Do healthcare exposures contribute to burden of new infections?. Issue 3 (7th January 2013) - Perz, Joseph F.; Grytdal, Scott; Beck, Suzanne; Fireteanu, Ana Maria; Poissant, Tasha; Rizzo, Elena; Bornschlegel, Katherine; Thomas, Ann; Balter, Sharon; Miller, Jeremy; Klevens, R. Monina; Finelli, Lyn
Abstract: Reports of hepatitis B virus (HBV) and hepatitis C virus (HCV) transmission associated with unsafe medical practices have been increasing in the United States. However, the contribution of healthcare exposures to the burden of new infections is poorly understood outside of recognized outbreaks. We conducted a case‐control study at three health departments that perform enhanced viral hepatitis surveillance in New York and Oregon. Reported cases of symptomatic acute hepatitis B and hepatitis C occurring in persons ≥55 years of age from 2006 to 2008 were enrolled. Controls were identified using telephone directories and matched to individual cases by age group (55‐59, 60‐69, and ≥70 years) and residential postal code. Data collection covered exposures within 6 months before symptom onset (cases) or date of interview (controls). Forty‐eight (37 hepatitis B and 11 hepatitis C) case and 159 control patients were enrolled. Case patients were more likely than controls to report one or more behavioral risk exposures, including sexual or household contact with an HBV or HCV patient, >1 sex partner, illicit drug use, or incarceration (21% of cases versus 4% of controls exposed; matched odds ratio [mOR] = 7.1; 95% confidence interval [CI]: 2.1, 24.1). Case patients were more likely than controls to report hemodialysis (8% of cases; mOR = 13.0; 95% CI: 1.5, 115), injections in a healthcare setting (58%; mOR = 2.7; 95% CI: 1.3, 5.3), and surgery (33%; mOR = 2.3; 95% CI: 1.1, 4.7). In a multivariate model, behavioral risks (adjusted OR [aOR] = 5.4; 95% CI: 1.5, 19.0; 17% attributable risk), injections (aOR = 2.7; 95% CI: 1.3, 5.8; 37% attributable risk), and hemodialysis (aOR = 11.5; 95% CI: 1.2, 107; 8% attributable risk) were associated with case status. Conclusion: Healthcare exposures may represent an important source of new HBV and HCV infections among older adults. (HEPATOLOGY 2013)